Ubiquilin 1 suppresses the cancer stem cell–like traits of non-small cell lung cancer cells by regulating reactive oxygen species homeostasis. Issue 1 (1st January 2021) - Liu, Ting; Ma, Qianqian; Li, Wenjie; Hu, Yan; Yang, Jun; Yao, Qi
ABSTRACT: Cancer stem cell (CSC) has been confirmed to trigger tumor occurrence and progression and CSC can develop strategies to maintain a lower reactive oxygen species (ROS) level compared to cancer cells. However, the mechanisms contributing to ROS homeostasis in CSC are still lacking key elements. In the current study, we found that reductive redox states and ROS levels were suppressed in non-adherent spheres formed by non-small cell lung cancer (NSCLC) cells, which were confirmed to hold CSC-like traits. However, mitochondria DNA content and cellular oxygen consumption rate analyses revealed fewer numbers of mitochondria in NSCLC spheres. Further exploration attributed this result to decreased mitochondrial biogenesis, likely resulted from the accelerated degradation of peroxisome proliferator-activated receptor γ coactivator 1α (PGC1α). Mechanistic studies indicated that Ubiquilin 1 (UBQLN1) increased PGC1α protein stability via reducing the ubiquitination of PGC1α protein. Moreover, UBQLN1 was lowly expressed in NSCLC spheres compared to that in parental NSCLC cells and UBQLN1 overexpression suppressed the CSC-like traits of NSCLC cells, which was characterized as the decrease of ALDH1 activity, sphere-formation ability, and CSC marker expression. Finally, clinical investigations further demonstrated that UBQLN1 level was positively correlated with patient's survival of lung adenocarcinoma, but not squamous cell carcinoma of lung. Taken together, our results revealed a novel mechanism involving ROS homeostasis and mitochondrial biogenesis in non-small cell lung CSCs, which may provide novel potential targets and methods for NSCLC patients.